Factors Influencing The Increase in Khulu's Divorce: A Case at The Jember Religious Court (2021-2023) - Badri, Muhamad Arifin; Burhanuddin, Anas; Jauhar, Ghufran (al-'adalah, 2024)
Divorce cases in Jember Regency over the past three years have reached a fantastic number and are among the highest in East Java. This study aims to find the causes of the high number of divorce lawsuits (khulu') in the Jember Religious Court, its implications and alternative solutions to reduce this phenomenon. This study is classified as qualitative research with a case study approach. Data were obtained through interviews with several religious court officials, court documentation, leading journals and information from other reliable sources. The results of the study indicate that economic problems and constant quarrels are the main factors among a number of factors that encourage the emergence of divorce lawsuits. The implication of this case is the neglect of hadlānah issues and the fulfillment of ex-wives’ rights by ex-husbands. In examining khulu' cases, judges tend to choose the al-tafrīq al-Qadlā scheme which allows them to protect the rights of ex-wives while requiring ex-husbans to meet the needs of children (hadlānah) and the 'iddahmaintenance of his ex-wife. Furthermore, to reduce the increase in divorce cases, there are three solutions can be taken. First, cooperate with zakat institutions to help overcome family economic problems, especially families who are in court. Second, increasing the role of the Job Training Center to equip husbands and wives with soft skills and hard skills so that they can earn a living. Third, maximizing family guidance at the Religious Affairs Office (KUA) for prospective brides and grooms, including those who are already married, to realize family resilience in facing various household problems